2009
DOI: 10.1091/mbc.e08-12-1204
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 Regulates Phagocytosis of Photoreceptor Outer Segments in the Mouse Retina

Abstract: The daily phagocytosis of shed photoreceptor outer segments by pigment epithelial cells is critical for the maintenance of the retina. In a subtractive polymerase chain reaction analysis, we found that functional differentiation of human ARPE19 retinal pigment epithelial (RPE) cells is accompanied by up-regulation of annexin (anx) A2, a major Src substrate and regulator of membrane-cytoskeleton dynamics. Here, we show that anx A2 is recruited to the nascent phagocytic cup in vitro and in vivo and that it fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 42 publications
1
76
0
2
Order By: Relevance
“…Protein recruitment can be assessed by immunofluorescence co-localization assays [13][14][15][19][20][21]37,41 ( Figure 3B). Protein recruitment or activation can be validated on immunoblots after immunoprecipitation or by checking for phosphorylation 7,10,[12][13][14][15]17,19,20,27,35,37,41 ( Figure 3C). More open-ended studies on overall gene expression changes after different times of POS challenge have also been performed 42 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…Protein recruitment can be assessed by immunofluorescence co-localization assays [13][14][15][19][20][21]37,41 ( Figure 3B). Protein recruitment or activation can be validated on immunoblots after immunoprecipitation or by checking for phosphorylation 7,10,[12][13][14][15]17,19,20,27,35,37,41 ( Figure 3C). More open-ended studies on overall gene expression changes after different times of POS challenge have also been performed 42 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…10,11 Given its high specificity, it has been widely used in studies addressing structure and function of rhodopsin, 12 as well as a reliable fusion tag for purification of nonrelated receptors. 13,14 In mice, it has been used for the detection of rhodopsin 15 and its subcellular distribution 16 during retinal degeneration. This antibody is commercially available (ab5417; Abcam, Cambridge, UK; R5403; Sigma-Aldrich, St. Louis, MO; sc-57,432; SCBT, Santa Cruz, CA; MAB5356; Millipore, Billerica, MA) and according to the supplier is used to detect rhodopsin also in zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…9 It binds to the C-terminal eight amino acids of rhodopsin and labels rod outer segments in mice, cows, and humans. 15,16 Recently, two zebrafish reports used this antibody as a predicted rod outer segment marker for functional studies on retinitis pigmentosa (RP) related genes. In the first study, the protein ZFPRGP was examined in the presumptive rod cilium region using 1D4 as a co-localizing marker.…”
Section: Discussionmentioning
confidence: 99%
“…44 Intracellularly, ANXA2 is present on the plasma membrane and early endosome and interacts with actin to act as a regulator of membra-cytoskeleton dynamics. [45][46][47] It was reported that ANXA2 is involved in the phagocytosis of the shed photoreceptor outer segment by pigment epithelial cells in the retina. 47 Furthermore, ANXA2 is known to be present in various cells such as endothelial cells, monocytes, macrophages, and most cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] It was reported that ANXA2 is involved in the phagocytosis of the shed photoreceptor outer segment by pigment epithelial cells in the retina. 47 Furthermore, ANXA2 is known to be present in various cells such as endothelial cells, monocytes, macrophages, and most cancer cells. 39,48,49 Asbestos is neither an intracellular pathogen that has developed specific ligand proteins to enter nonprofessional phagocytes nor an apoptotic body that arises during the normal physiological state and has a phagocytic removal system through nonprofessional phagocytes.…”
Section: Discussionmentioning
confidence: 99%